QUERCETIN EFFECTS ON WEIGHT GAIN AND CALORIC INTAKE IN EXERCISED RATS - R.A. Casuso; E.J. Martínez-López; F. Hita-Contreras; D. Camiletti-Moirón; A. Martínez-Amat (Termedia Publishing House, 2014)
Quercetin is a flavonoid which activates oxidative metabolism. Quercetin may reduce weight gain by decreasing feed efficiency. The present study aims to evaluate weight gain, caloric intake and feed efficiency in exercised and sedentary rats supplemented with quercetin. Wistar rats were divided into four groups: quercetin-exercise training (QT), quercetin-sedentary (QS), placebo-exercise training (PT) and placebo-sedentary (PS). Rats were exercised and/or orally supplemented with quercetin (25 mg · kg-1 on alternate days) during six weeks. Weight gain of the QT group decreased when compared with the PT and PS groups. Exercised groups increased cumulative caloric intake during the experimental period. The QT group rats also reduced their feed efficiency when compared with the QS and PS groups. These results suggest that quercetin is not able to decrease weight gain because no differences were found between placebo and quercetin condition either in the sedentary or in the training condition.